Effect of cigarette smoke extract and hypoxia on vasoactive gene expression and mediator release in human pulmonary artery smooth muscle and endothelial cells - Alqarni, Abdullah Abdulghani M. (2020)
Background: Pulmonary hypertension is a common and serious complication of COPD. Studies suggest that hypoxia and cigarette smoke (CS) can cause vascular remodelling in COPD as a result of cell proliferation; however, the underlying cause is not fully understood. In addition, it is suggested that the use of e-cig may lead to vascular diseases, but no data are available on what effect e-cig may have on dysfunction of pulmonary artery smooth muscle cells (PASMCs) and pulmonary artery endothelial cells (PAECs). Thus, we hypothesise that cigarette smoke extract (CSE) and hypoxia can induce imbalanced vasoactive gene expression and mediator release, and then contribute to cell proliferation and apoptosis. Furthermore, e-cig vapour extract with and without nicotine (ECVE-/+n) may have similar effects as CSE.